Microglial exosomes alleviate intermittent hypoxia-induced cognitive deficits by suppressing NLRP3 inflammasome - Yaodan Zhang; Yuyang Miao; Xiangyang Xiong; Jin Tan; Zhaoli Han; Fanglian Chen; Ping Lei; Qiang Zhang (Biology Direct, 2023)
Abstract Intermittent hypoxia is the best predictor of developing cognitive decline and Alzheimer’s disease progression in patients with obstructive sleep apnea. The nucleotide-binding oligomerization domain-like receptor 3 (NLRP3) inflammasome has been poorly studied as a regulator of neuroinflammation in cognitive impairment caused by intermittent hypoxia. As critical inflammatory cells, exosomes secreted by microglia have been found to affect the spread of pathologic proteins and neuropathology in neurodegenerative diseases. However, the effects of microglial exosomes on neuroinflammation and cognitive outcomes after intermittent hypoxia remain unclear. In this study, the role of miRNAs in microglial exosomes in improving cognitive deficits in mice exposed to intermittent hypoxia was investigated. We demonstrated that miR-146a-5p fluctuated over time in microglial exosomes of mice exposed to intermittent hypoxia for different periods of time, which could regulate neuronal NLRP3 inflammasome and neuroinflammation. In primary neurons, we found that miR-146a-5p regulated mitochondrial reactive oxygen species by targeting HIF1α, thus affecting the NLRP3 inflammasome and secretion of inflammatory factors. Similarly, further studies showed that inhibition of NLRP3 by administering overexpressed miR-146a-5p in microglial exosomes and MCC950 has improved neuroinflammation and cognitive dysfunction in mice after intermittent hypoxia. In conclusion, NLRP3 inflammasome may be a regulatory target for ameliorating cognitive impairment caused by intermittent hypoxia, and microglial exosomal miR-146a-5p may be a promising therapeutic strategy.